Trade-Unions in an Age of Pluralism and Structural Change : The Response to the Irrepressible Demands of the Common Man - Barkin, Solomon (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1971)
Reviewing the industrial unrest of the last three years in Western Europe and the United States, the author describes and analyses the new trends in the trade-union movement to cope with such a new situation.